Evaluating the Efficiency of Work of the Department of Computed Tomography and Magnetic Resonance Imaging - K. K. Osadchiy; E. A. Mershina; A. E. Bragina; V. E. Sinitsyn (Вестник рентгенологии и радиологии, 2019)
Objectives. (1) To evaluate the efficiency of work of the Department of Computed Tomography (CT) and Magnetic Resonance Imaging (MRI); (2) to study of its work processes; and (3) to elaborate recommendations for their optimization.Material and methods. Using the principles of lean manufacturing and the original methodology of the Philips Co., the investigators made a comprehensive assessment of the work of the Tomography Department, Center for Radiation Diagnosis, Treatment and Rehabilitation, Ministry of Health of the Russian Federation, in December 2016 to February 2017, including: (1) a study of management reports; (2) oral interviews of employees; (3) a survey of employees, by using a specially designed questionnaire; (4) direct observation and subsequent description of work processes; and (5) assessment of patient satisfaction, by calculating the net promoter score. Based on the findings, the investigators calculated the throughput potential of CT and MRI, described the factors influencing the possibility of realizing this potential, developed recommendations to enhance the efficiency of work processes, and ranked the latter by the magnitude of the expected effect, by the complexity of implementation, and by material costs, followed by prioritization.Results. Assessment of the throughput potential has shown that CT and MRI examinations can be performed by 50.6% and 23.2% more, respectively. This can be achieved by additionally attracting patients, reducing equipment downtime, optimizing work processes, most of all at the stage of patient recording and registration, as well as at the stage of image interpretation and creation of a conclusion. The developed recommendations for optimizing work processes included measures of varying effectiveness and complexity, which could rank them according to three priority levels and identify long-term strategic initiatives.Conclusion. The comprehensive study of the efficiency of work of the Departments of CT and MRI made it possible to quantify the potential for increasing the throughput of CT and MRI, to consider in detail the stages of a medical service delivery process, to reveal areas for improving the process, and to form a set of recommendations for their optimization.